Textual Analysis of Power of the Government of Indonesia and Aceh in the Helsinki MoU - Rosaria Mita Amalia (TEKNOSASTIK, 2019)
Ethno-national conflict in Aceh struggling for independence from the Unitary State of the Republic of Indonesia was waged for almost three decades since 1976. The military approach taken by the Government of Indonesia (GOI) for years was unable to bring the conflict to an end. Since then, conflict resolution through diplomatic mechanism was initiated by involving third party mediator. The massive natural disasters, earthquake and the tsunami that hit the region in December 2004 prior to the peace agreement between Government of Indonesia and GAM (Free Aceh Movement). The parties committed to agree the memorandum of understanding which known as Helsinki MoU. This research questions whose party more powerful is, Government of Indonesia or Aceh The question can be answered by using Critical Discourse Analysis as a tool. The linguistics instruments can show power which is dominated or not by one of the parties. Based on the findings in this study, it is confirmed that no one from two parties is more powerful than another. It is shown that the power between GOI and GAM is balanced. In other words, based on the analysis of MOU Helsinki, their position is adequate.